The impact of training informal health care providers in India: A randomized controlled trial - Das, Jishnu; Chowdhury, Abhijit; Hussam, Reshmaan; Banerjee, Abhijit V (Science (American Association for the Advancement of Science), 2016)
Health care providers without formal medical qualifications provide more than 70% of all primary care in rural India. Training these informal providers may be one way to improve the quality of care where few alternatives exist. We report on a randomized controlled trial assessing a program that provided 72 sessions of training over 9 months to 152 informal providers (out of 304). Using standardized patients ("mystery clients"), we assessed clinical practice for three different conditions to which both providers and trainers were blinded during the intervention, representative of the range of conditions that these providers normally diagnose and treat. Training increased correct case management by 7.9 percentage points (14.2%) but did not affect the use of unnecessary medicines and antibiotics. At a program cost of $175 per trainee, our results suggest that multitopic medical training offers an effective short-run strategy to improve health care.